Learning Program Quality and Knowledge Dissemination Under the “RU for All” Learning Center: Bridging Communities through Sustainable Learning - Masantiah, Chuthaphon; Wisessathorn, Manika; Poompin, Kritchaya; Benjaphong, Wanatphong (Ratchaphruek Journal, 2026)
This study aimed to: 1) Assess the quality of learning programs under the “RU for All” Learning Center: bridging communities through lifelong learning; and 2) Compare the outcomes of knowledge dissemination across different programs. The participants for the program quality assessment included 20 teachers, staff, and network schools from the Faculty of Education in Bangkok, as well as 20 community participants, totaling 40 individuals. Data were collected using a five-point Likert scale questionnaire and analyzed with descriptive statistics, means, and standard deviations. For comparing knowledge dissemination outcomes, 108 participants were randomly selected. Sample size was calculated using G*Power 3.1.9.4 for a one-way analysis of variance with an effect size of 0.45, a significance level of .05, and a statistical power of .80. Data were collected using a five-point Likert-scale questionnaire and analyzed using descriptive statistics (mean and standard deviation) and inferential statistics, specifically one-way analysis of variance (ANOVA) with the F-test. The results revealed that: 1) Overall learning program quality was rated at the highest level with all aspects-content, instructional methods, learning materials, and assessment-also rated highly. 2) Knowledge dissemination outcomes were also rated at the highest level overall , and no significant differences were found among the programs.